A comparison between microscopical and ELISA technique in diagnosis of Giardia lamblia infection with epidemiological and biochemical study among Children under ten years in Tikrit District - Sinai Najy Muhsin; Ibrahim Sh. Daoud (Tikrit Journal of Pure Science, 2023)
The current study includes 644 stool samples of patients infected with diarrhea less than ten years old who are attended Tikrit Teaching Hospital from 1/12/2008 to 30/6/2009. Three methods are used for the examination of stool, the first one is the direct microscopical test. The number of samples which are tested are 55 with the percentage of 8.54%. The second is the floatation method with three solution[ Zinc Sulphate solution, Sucrose solution, and Sodium chloride solution] The number of samples which are tested by floatation method are 64 with the percentage of 9.94%. The third is ELISA method to detect parasite antigen in stool. The number of samples which are tested by this methods are 80 with the percentage of 12.42%. The results show there are significant difference between infected patients  with giardiasis and the healthy persons group and for significant level 0.05<p in the mentioned tests. The study points out a decrease in both Hb, PCV and an increase in the rate of  WBCc and ESR . The study point out a decrease in the rate of Ca++,  Mg++, Na+, Tp, Chol. And Tri.  and an increase in the rate concentration of GOT, GPT.